Correlation between Application of Audiolingual Method and the Task-Based Learning Method in Arabic Language Learning and Student Learning Achievement in Junior High Schools - Maftukh Ghulam Mursyidan; Dahayu Fauziyah Candrawati; Mas Achmad Yusril Insan Kamil; Hisbullah Huda Mursyidan; Anisah Firdausi Nuzula (Institut Nurul Islam, 2026)
This study aims to determine the correlation between the application of Audiolingual and Task-Based Learning methods in Arabic language learning with student learning achievement in Junior High Schools. The study used a quantitative approach with a correlational design. The research sample consisted of 23 ninth-grade students selected using a purposive sampling technique. Data collection was carried out through a Likert scale questionnaire and documentation of Arabic language learning outcomes. Data were analyzed using the Shapiro-Wilk normality test and the Spearman Rank correlation test with the help of the JASP application. The results showed a positive and significant correlation between the application of Audiolingual and Task-Based Learning methods with student learning achievement, with a correlation coefficient value of 0.995 and a significance of 0.001 <0.05. It was concluded that the application of both methods can support more active, communicative, and effective Arabic language learning so that it is related to increased student learning achievement.